Peran Brand Preference Memediasi Pengaruh Co-Branding dan Brand Equity Terhadap Minat Beli: (Studi Pada Kolaborasi Indomie dan Pop Mie) - Tuzzahro, Aminah; Zawir Simon, Zainal (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study aims to see effect of co-branding and brand equity on purchase intention through brand preference as an intervening variable. Data analysis using Partial Least Square Structural Equation Modeling (PLS-SEM). The results showed that: (1) co-branding has a positive and significant effect on brand preference, (2) brand equity has a positive and significant effect on brand preference, (3) co-branding has no effect on purchase intention, (4) brand equity has a positive and significant effect on purchase intention, (5) brand preference has a positive and significant effect on purchase intention, (6) brand preference mediates the effect of co-branding on purchase intention, (7) brand preference mediates the effect of brand equity on purchase intention.